2011
DOI: 10.1309/ajcpyi1z3tggaiep
|View full text |Cite
|
Sign up to set email alerts
|

Lossless Compression of JPEG2000 Whole Slide Images Is Not Required for Diagnostic Virtual Microscopy

Abstract: The use of lossy compression in medical imaging is controversial, although it is inevitable to reduce large data amounts. In contrast with lossy compression, lossless compression does not impair image quality. In addition to our previous studies, we evaluated virtual 3-dimensional microscopy using JPEG2000 whole slide images of gastric biopsy specimens with or without Helicobacter pylori gastritis using lossless compression (1:1) or lossy compression with different compression levels: 5:1, 10:1, and 20:1. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Luckily, it is generally not prohibited by the main regulatory bodies in the European Union, United States, Canada, and Australia, provided that it does not impair the diagnostic quality and does not cause new risks compared with conventional practice. 8 Hence, it is important to define a strategy or protocol for an efficient parameterization of the deployed compression techniques to yield a high compression ratio without jeopardizing the classification performance. The issue of higher compression ratio with lower encoding time has been recognized as well in recent efforts for creating the DICOM standard in the field of digital pathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luckily, it is generally not prohibited by the main regulatory bodies in the European Union, United States, Canada, and Australia, provided that it does not impair the diagnostic quality and does not cause new risks compared with conventional practice. 8 Hence, it is important to define a strategy or protocol for an efficient parameterization of the deployed compression techniques to yield a high compression ratio without jeopardizing the classification performance. The issue of higher compression ratio with lower encoding time has been recognized as well in recent efforts for creating the DICOM standard in the field of digital pathology.…”
Section: Introductionmentioning
confidence: 99%
“…9 For studying the impact of lossy compression on the diagnostic performance of human experts, several studies have been reported. 8,[10][11][12][13][14][15][16] Mostly, they reported that the human visual perception is to some extent robust against image quality degradation. However, there is not a generally accepted tolerance level with respect to the diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used lossy image compression is JPEG and an example of a lossless compression is PNG. High-quality lossy compression can be sufficient for image processing, [14] but lossless compression is recommended. [8] We used 90% lossy compression (JPEG format) for the 20x WSIs which was sufficient for our analysis; lower quality settings were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…For large virtual tissues, a format that satisfies many limited bandwidth and image fidelity requirements is the JPEG2000 standard, where compression ratios of thirty-to-one can often be used without a large sacrifice in image quality (Tuominen and Isola, 2009). This standard has also been successfully applied in digital pathology using a twenty-to-one compression ratio of three-dimensional whole-slide pathology images (Kalinski et al, 2011). Current formats that support the JPEG2000 standard are MBF Bioscience's JPX and Aperio's SVS formats.…”
Section: Assessing Internet Environment and Optimizing Imagesmentioning
confidence: 99%